Chemokine homolog of molluscum contagiosum virus: sequence conservation and expression - Bugert, Joachim J.; Lohmüller, Claudia; Damon, Inger; Moss, Bernard; Darai, Gholamreza (Virology, 1998)
An analysis of the complete Molluscum contagiosum virus (MCV-1) genome sequence revealed a 104-amino-acid open reading frame (MC148R) that is structurally related to the β (CC) family of chemokines. The predicted MCV chemokine homolog (MCCH) has a deletion in the NH2-terminal activation domain, suggesting the absence of chemoattractant activity. The principal objectives of the present study were to determine whether: (i) MCCH is conserved in independent isolates of MCV-1 and MCV-2; (ii) MCCH mRNA is expressedin vivo;and (iii) the MCCH protein is secreted from mammalian cells. The nucleotide sequence of the MCCH gene locus was determined for 27 isolates of MCV-1 and 2 of MCV-2 obtained from 29 MCV-infected individuals. In each case, the characteristic CC sequence, the NH2-terminal deletion, and the length of the open reading frame were conserved, although there were some, mostly conservative, amino acid substitutions. Since MCV cannot be propagated in cell culture, mRNA was synthesizedin vitroby the early transcription apparatus in purified MCV virions. MCCH RNA was amplified by RT-PCR; the sequence included the complete open reading frame and extended 40 to 50 nucleotides past the first poxviral termination signal (TTTTTNT). Similar RT-PCR results were obtained using total cellular RNA derived from MCV-infected tissue specimens. Finally, the MCCH open reading frame was expressed in a vaccinia virus vector and the predicted size polypeptide was secreted into the medium, as determined by Western blotting. Taken together, our data support the prediction that MCV expresses a secreted chemokine homolog that could antagonize the inflammatory responsein vivo.
Elektronische Reproduktion der Druck-Ausgabe 25. Mai 2002
Gesehen am 05.09.2024